Are Silent Inflammations Responsible for Chronic Civilisation Diseases? - Manfred , Doepp (Research Highlights in Disease and Health Research Vol. 7, 2023)
Inflammation is an evolutionarily conserved process characterized by the activation of immune and non-immune cells that protect the host from bacteria, viruses, toxins and infections by eliminating pathogens and promoting tissue repair and recovery. Chronic silent inflammations are the killer diseases number one. These include immune system dysfunction with regulations disorders, autoaggressions, allergies, and as an underlying disease, mitochondriopathy. For about 2 years, we have been noticing more and more frequently that patients have antibodies against mitochondrial RNA and/or DNA. A connection with the mRNA vaccinations may exist. Unvaccinated persons also exhibit this phenomenon. One can think of "vaccine shedding". In parallel, a population spike protein infestation is underway. These affect the ACE2 receptors of many organs, including the heart muscle. Therefore, the frequency of myocardial weaknesses is increasing. We have developed a means of treatment that has been known for 2000 years. It is a tincture of frankincense, myrrh and colloidal gold. There was a significant decrease in antibody titers in affected patients. It seems that the autoimmune processes respond positively to these ingredients. Against the spike proteins problems we developed a tincture containing esp. dandelion extract and pine needle extract. For the prevention of heart failure, strophanthin/ouabain has been shown to be best (3 mg gastric juice-resistant capsules). These three agents are also effective in post covid or long covid symptoms.